Strategi Pengembangan Ekowisata Bale Mangrove Dalam Meningkatkan Jumlah Kunjungan Wisatawan Di Dusun Poton Bako, Jerowaru, Lombok Timur - Yuniati, Yuniati; Murdana, I Gede (JURNAL DESTINASI PARIWISATA, 2024)
Mangrove ecotourism is one form of tourism that can be developed in Indonesia this research aims to find out what strategies, supporters and obstacles are applied and faced by mangrove bale ecotourism to develop the ecotourism to be better known by local, national and foreign tourists. This research uses Qualitative Research, which is research that produces descriptive data in the form of written or spoken words from people and behaviors that can be observed by taking a qualitative approach. The types of data used in this research are primary data and secondary data through observation, interviews and documentation, which can be obtained directly from pokdarwis, pokmaswas, tourists, reports and photographs. The data collection technique used is non-participant observation, which is an indirect researcher. From the results of the research conducted, it can be concluded that the mangrove bale ecotourism development strategy carried out by Pokdarwis and pokmaswas in increasing the number of tourist visits in Poton Bako hamlet, Jeroawaru as follows: (1) collaborating with the central government, vocational schools and universities as a channel to introduce mangrove bale ecotourism, (2) promoting mangrove bale ecotourism through social media such as Facebook, Instagram, Tiktok and Google my Business. In addition, there are supporting factors, namely support from the central government, unspoiled natural beauty and tour packages provided such as Explore Mangrove, Mangrove Camp, Mangrove Edutour, Explore Teluk Jukung and canoe racing while inhibiting factors are the lack of support from local and village governments and the lack of adequate human resources to support the development of mangrove bale ecotourism. Keywords: Development Strategy, Ecotourism, Tourists